2008
DOI: 10.1002/adsc.200800575
|View full text |Cite
|
Sign up to set email alerts
|

Supported Palladium Catalysts for Suzuki Reactions: Structure‐Property Relationships, Optimized Reaction Protocol and Control of Palladium Leaching

Abstract: Palladium on metal oxides and on activated carbon with particular properties (high palladium dispersion, low degree of reduction, water content) are shown to be highly active (tunrover number, TON = 20,000; turnover frequency, TOF = 16,600), selective and robust catalysts for Suzuki cross-couplings of aryl bromides and activated aryl chlorides. Catalysts and reaction protocol offer combined advantages of high catalytic efficiency under ambient conditions (air and moisture), easy separation and reuse and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(91 citation statements)
references
References 51 publications
2
87
0
Order By: Relevance
“…For instance, Pd leaching under aryl halide action found earlier for the Heck reaction should theoretically (based on scheme 3) occur in the Suzuki reaction. Numerous confirmations of this were, indeed, found, 4,7,10,31,32 moreover the correlation between the activity and the amount of However, from the previous discussion of the Heck chemistry, it can be concluded that distinguishing between true homogeneous catalysis from heterogeneous catalysis in the Suzuki reaction is undoubtedly a very complicated task. Unfortunately, the results of the conventional tests on reaction homogeneity-heterogeneity 33 are ambiguous due to the interconversions of different catalyst forms (Scheme 3).…”
Section: Scheme 2 Heck Reactionmentioning
confidence: 80%
See 2 more Smart Citations
“…For instance, Pd leaching under aryl halide action found earlier for the Heck reaction should theoretically (based on scheme 3) occur in the Suzuki reaction. Numerous confirmations of this were, indeed, found, 4,7,10,31,32 moreover the correlation between the activity and the amount of However, from the previous discussion of the Heck chemistry, it can be concluded that distinguishing between true homogeneous catalysis from heterogeneous catalysis in the Suzuki reaction is undoubtedly a very complicated task. Unfortunately, the results of the conventional tests on reaction homogeneity-heterogeneity 33 are ambiguous due to the interconversions of different catalyst forms (Scheme 3).…”
Section: Scheme 2 Heck Reactionmentioning
confidence: 80%
“…Now it is quite clear that there is no consensus on the nature of the catalysis of this reaction (see review 2 published in 2006 and references cited therein). Analysis of the literature for the last two years indicates that some researchers advance the hypothesis of a homogeneous catalysis mechanism [3][4][5][6][7][8][9][10][11] while the others suggest a heterogeneous mechanism. [12][13][14][15][16][17][18] It is worth mentioning that the most convincing evidence is for the homogeneous mechanism of the Suzuki reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligand-free and recyclable heterogeneous Pd catalysts represent promising options to address these issues [174,175]. The Pd NPs supported on some traditional carbon materials such as mesoporous carbon [176], AC [177], and CNTs [8] to induce coupling reactions have been developed into a distinct research area. Recently, a number of graphenebased hybrids were synthesized and employed for coupling reactions.…”
Section: C-c Coupling Reactionsmentioning
confidence: 99%
“…To address this issue, heterogeneous catalysts have provided a desirable alternative regarding their recyclability, less contamination to the products, cost benefits and environmental acceptability. Palladium species including palladium nanoparticles and palladium(II) ion could be heterogenized on the surface of the support materials such as ionic liquids, [17] zeolites and molecular sieves, [18] activated carbon, [19] metal oxides, [20] graphene oxide, [21] clays,433 polymers. [24] However, the reaction performance of the heterogeneous catalysts was affected signally by the intrinsic properties of the support materials as well as the links between the active components and the support.…”
mentioning
confidence: 99%